2011
DOI: 10.17221/3/2011-pps
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and biochemical impacts of some new insecticide mixtures on cotton leafworm Spodoptera littoralis (Boisd.)

Abstract: Abd El-Mageed A.E.M., Shalaby S.E.M. (2011): Toxicity and biochemical impacts of some new insecticide mixtures on cotton leafworm Spodoptera littoralis (Boisd.). Plant Protect. Sci., 47: 166-175.The susceptibility to five new insecticide mixtures: chlorosan, feroban, cygron, engeo, and kingbo was studied in the 2 nd and 4 th instar larvae of the cotton leafworm Spodoptera littoralis (Boisd.). The efficiency and residual effects of these compounds against S. littoralis under field conditions were also investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…In addition results showed that the 2 nd instar larvae were more susceptible to tested oils than the 4 th instar larvae. These results of the effectiveness of tested essential oils coincide with those obtained by other authors (Abd El-Aziz and Ezz El-Din, 2007;Marei et al, 2009;Abd El-Mageed and Shalaby, 2011;Shabnum and Wagay, 2011;Hassan, 2012;Khedr and El-Kawas, 2013;Abdel-Aziz et al, 2013;and Ali et al, 2017). The efficacy of the applied oils met these criteria for the applied dipping assays.…”
Section: Virulence Of the Tested Compounds Against The Cotton Leaf supporting
confidence: 90%
“…In addition results showed that the 2 nd instar larvae were more susceptible to tested oils than the 4 th instar larvae. These results of the effectiveness of tested essential oils coincide with those obtained by other authors (Abd El-Aziz and Ezz El-Din, 2007;Marei et al, 2009;Abd El-Mageed and Shalaby, 2011;Shabnum and Wagay, 2011;Hassan, 2012;Khedr and El-Kawas, 2013;Abdel-Aziz et al, 2013;and Ali et al, 2017). The efficacy of the applied oils met these criteria for the applied dipping assays.…”
Section: Virulence Of the Tested Compounds Against The Cotton Leaf supporting
confidence: 90%
“…The experiments that used to study the toxicity of the 5‐imidazolinone derivatives (1‐18) against “the second instar larvae of S . littoralis ” occurred by the “the leaf dip technique” . In this technique, the emulsions of the synthesized compounds in water containing 0.1% triton X‐100 were prepared and immediately used.…”
Section: Resultsmentioning
confidence: 99%
“…The 24 h exposure, however, was still sufficient for causing significant sublethal effects, especially in females exposed to concentrations of 34.3 μl/l and 24 μl/l. In laboratory bioassays, oxymatrine and/or oxymatrine-based products have shown considerable toxic and antifeedant activity against several insect pest species (Mao and Henderson, 2007;Asghari-Tabari et al, 2009;Abd El-Mageed and Shalaby, 2011). The only available information on their acute toxicity to mites had been reported by Wang et al (2009), who found the combination of oxymatrine/psoralen to have an LC 50 of 150 μg/l for carmine spider mite, T. cinnabarinus.…”
Section: Resultsmentioning
confidence: 99%